Clinical applications of intravenous immunoglobulins in neurology - Hughes, R A C (Blackwell Science Inc, 2009)
Intravenous immunoglobulin (IVIg) is used increasingly in the management of patients with neurological conditions. The efficacy and safety of IVIg treatment in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and Guillain–Barré syndrome (GBS) have been established clearly in randomized controlled trials and summarized in Cochrane systematic reviews. However, questions remain regarding the dose, timing and duration of IVIg treatment in both disorders. Reports about successful IVIg treatment in other neurological conditions exist, but its use remains investigational. IVIg has been shown to be efficacious as second-line therapy in patients with dermatomyositis and suggested to be of benefit in some patients with polymyositis. In patients with inclusion body myositis, IVIg was not shown to be effective. IVIg is also a treatment option in exacerbations of myasthenia gravis. Studies with IVIg in patients with Alzheimer's disease have reported increased plasma anti-Aβ antibody titres associated with decreased Aβ peptide levels in the cerebrospinal fluid following IVIg treatment. These changes at the molecular level were accompanied by improved cognitive function, and large-scale randomized trials are under way.